1994
DOI: 10.1136/hrt.71.6.531
|View full text |Cite
|
Sign up to set email alerts
|

Direct access exercise electrocardiography: a new service that improves the management of suspected ischaemic heart disease in the community.

Abstract: Direct access exercise electrocardiography for patients with suspected ischaemic heart disease is safe, feasible, and helpful to general practitioners. This service seems to reduce the number of patients referred to cardiology outpatient clinics and to facilitate the management of these patients in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…This is in keeping with the findings of previous smaller studies which showed the difficulty of identifying left ventricular systolic dysfunction clinically 5 6. The rate of positive findings compares favourably with other reported direct access cardiac investigations such as exercise testing 13. A negative finding is also important, however, since it allows inappropriate treatment to be withdrawn.…”
Section: Success Of Servicesupporting
confidence: 62%
See 1 more Smart Citation
“…This is in keeping with the findings of previous smaller studies which showed the difficulty of identifying left ventricular systolic dysfunction clinically 5 6. The rate of positive findings compares favourably with other reported direct access cardiac investigations such as exercise testing 13. A negative finding is also important, however, since it allows inappropriate treatment to be withdrawn.…”
Section: Success Of Servicesupporting
confidence: 62%
“…In a comparable study of open access exercise testing only 140 patients were seen in two years 13. The demand for our service has been stable and the projected yearly total of patients is about 600.…”
Section: Success Of Servicementioning
confidence: 92%
“…However, some groups have been cautious about providing open access echocardiography to general practitioners without an accompanying clinical assessment [1]. We and others have previously shown that general practitioners generally use open access stress electrocardiography appropriately and that referring GPs find it a useful service [2]. A number of groups have reported their experience of open access echocardiography [3 -5].…”
Section: Introductionmentioning
confidence: 98%
“…Direct access to exercise testing was offered to 122 general practitioners in Belfast, and over two years 192 patients (a remarkably small number) were assessed 1. Only 18% of tests gave positive results.…”
Section: Ordering Tests Is Easy But a Specialist's Opinion May Be Momentioning
confidence: 99%